Parametric models for investigation of contact interaction of elements stamp tools - Демина, Наталья Анатольевна (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2014)
A new approach to modeling of contact interaction of bodies is proposed. Parameterization methodology was developed to provide variativity. It covers all stages of the research. In particular, the results of stress-analisis for a system of three bodies are presented as an example for die equipment. Форма пуансона была выбрана в виде цилиндра, заготовки – круглой пластины, матрица – полый цилиндр с утолщением на конце. The shape of the punch was chosen as the cylinder blank - circular plate matrix - a hollow cylinder with a thickening at the end. The problem is solved in axisymmetric formulation based on an axial symmetry of the construction, loads and boundary conditions. Calculation scheme of the problem was constructed, that was calculated in the software ANSYS. To describe the behavior a linear elastic material model is used, and a stuff is defined for each of the elements. Generalized parametric modeling approach is adapted to provide a variation of investigated objects –all the varied factors of the model of the investigated process or condition considered as generalized parameters. The set of these parameters generates a generalized parametric space, each point of that identifies the analyzed model. Defined in the parameter space for a discrete set of points, it is possible to organize the process of numerical studies, working in automated mode. Using the proposed approach stress-strain state investigation of the elements of the system "matrix - material - punch" were held